Gothic Elements in the Setting of Joan Lindsay’s Novel Picnic at Hanging Rock - Ahmad , Hafidh Dwi; Yeni, Marliza; Sandika, Edria (Program Studi Sastra Inggris, 2025)
Joan Lindsay’s novel Picnic at Hanging Rock (1967) has been widely known in Australia as one of the best gothic novels. This research focuses on analyzing the elements of gothic found in Picnic at Hanging Rock to show the significance of the gothic elements in Australian literature. Taking this novel as the source of primary data, this research applies the theories of genre by Stephen Neale and gothic elements by Robert Harris. The primary data are analyzed by using textual analysis method, which involves close reading of the novel’s settings as the strong point in making the novel classified as a gothic literature. The result of analysis shows that Picnic at Hanging Rock relies a lot on the setting to present its gothic atmosphere. The two settings in the story, Appleyard College and the Hanging Rock grounds, completely embrace the gothic elements, which are: the setting in the horror place, the atmosphere of mystery, the supernatural incident, sentimental emotion, the omens, portents and visions, women in suffering, the use of gothic vocabulary, and hyperbolic phrases. All these elements are closely related with Australian setting, which is the Australian bush. It emphasizes that this novel gains its popularity as gothic novel because of strong gothic elements used in the setting of the novel, which are primarily related with Australian bush.